Analysis of the impact of fluctuations in the prices of crude oil in the international market on the public revenues in the Iraqi economy for the period (2003 - 2015) - يوسف التميمي, علـــي ثجيل; الكاظمي النجفي أبادي, مصطفى (lark, 2019)
AbstractThe adoption of the Iraqi economy on oil revenues is not new, but oil is the nerve of life for the national economy and the source of the most important and important in generating this national income on the one hand, and on the other is the main source and the basic no alternative in providing the foreign currency necessary in the financing of imports. Oil remains one of the main and important factors in the progress of Iraq and its political and social stability. And that the objective of the study analysis of oil price changes can have a negative impact on consumption, investment and unemployment. A sustained and sustained rise in oil prices may cause a change in the productive structure and have profound effects on economic stability. As for the problem of the study, the Iraqi oil sector suffers from a wide backwardness of the existence of multiple problems where the oil policy over the past decades to overcome them. The importance of the study lies in the importance of the oil sector in the present Iraqi economy by obtaining financial revenues (revenues) confirming the continued economy of Iraq to obtain oil revenues with a successful oil policy to solve all problems and build a successful oil sector. The most important result of the study is the dependence of the Iraqi economy on the oil sector and the revenues derived from it. All economic sectors are dependent on the degree of their development on this natural resource. This is the dominance of rents on the Iraqi economy with the beginning of economic planning and it continued until now and the future, as long as oil revenues feed government spending Growing.
Keywords: Analysis of volatility; oil prices; international market; public revenues; the Iraqi economy